The Relationship Between Soluble Interleukin-17 Receptor Levels and CD3-Positive T Cells and Lymphocytes in Patients with Sepsis and Their Predictive Clinical Significance - Li G; Zhang W; Gu W (Dove Medical Press, 2024)
Guixian Li,1 Wenbo Zhang,2 Wei Gu2 1Department of Critical Care Medicine, Baoding First Central Hospital, Baoding, Hebei Province, People's Republic of China; 2Department of Emergency Medicine, Chuiyangliu Hospital Affiliated to Tsinghua University, Beijing, People's Republic of ChinaCorrespondence: Wei Gu, Department of Emergency Medicine, Chuiyangliu Hospital Affiliated to Tsinghua University, No. 2 of Chuiyangliu South Street, Chaoyang District, Beijing, People's Republic of China, Tel +86 13633382381, Email weigugwgw@126.comBackground: To assess the relationship between soluble interleukin-17 receptor (sIL-7R) levels and CD3-positive t cells and lymphocytes in patients with sepsis and their predictive clinical significance.Methods: The study cohort comprised individuals diagnosed with sepsis based on the Third International Consensus Definitions for Sepsis and Septic Shock, treated in the emergency and critical care medicine departments at Beijing Chuiyangliu Hospital and Baoding No. 1 Central Hospital between December 2020 and June 2022. Patient outcomes were classified based on survival or mortality. Biomarkers, including sIL-7R levels and illness severity scores, were documented. All statistical analyses, including predictive modeling and comparisons were carried out using SPSS v.23.0 software and R software.Results: On the fifth day post-admission, sIL-7R levels significantly decreased in both the survival and death groups, compared with levels on day one (2.09 ± 0.65 vs 1.07 ± 0.53 ng/mL, P < 0.01). There was a significant correlation between the sIL-7R level and the CD3+ T-lymphocyte count (CD3+) (r = 0.44) and lymphocyte count (LYM) (r = 0.42). The combination of the sIL-7R level with the Sequential Organ Failure Assessment (SOFA) score demonstrated optimal predictive value for clinical outcomes in patients with sepsis, demonstrated by an area under the receiver operating characteristic curve of 0.998.Conclusion: sIL-7R levels are correlated with CD3+ and LYM counts. Additionally, the combination of serum sIL-7R level and SOFA score provides a robust method for predicting sepsis outcomes.Keywords: immune function, prognosis, sepsis, soluble interleukin-7 receptor